Caso de estudio: análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Alcazar Ancieta, Jimena Pamela (2019)
Nowadays, thanks to globalization, different markets and industries can communicate and generate business with each other globally. In addition, free trade agreements between countries make it easier for companies to access new markets to boost the economy and also, increase the percentage of employment for society. This paper will perform an analysis and diagnosis of the Peruvian Agribusiness Camposol where a strategic plan for the company in the next 5 years from the year 2019 will be developed. Camposol is a company with over 20 years of experience in its industry, which knows the market and quickly adapts to changes by internal and external factors. The company differentiates itself from its competition for the quality of its products and the full service that it provides to its customers through its strategically located offices in different parts of the world.